Teaching games for understanding (TGfU) developing gross motor skill In physical education - Fitrianto, Ari Tri; Habibie, Muhammad; Prayoga, Hegen Dadang (STKIP Paasundan Press, 2023)
The purpose of this study was to identify the TGfU approach to improve gross motor skills in elementary school children. The method used in this research is experimental method. The population of this research data is third grade students of Sungai Miai 4 Banjarmasin public elementary school, totaling 22 students with a research sample of 22 students with total sampling technique. Based on the results of data analysis obtained and discussion of research, that there is an effect of TGfU approach to gross motor skills of children. Although the study showed significant improvement, environmental factors, such as school and home environment, as well as parental influence, may affect the results. This study underscores the central role of play in developing children's motor skills, in line with previous research findings. Therefore, play-focused learning can be an effective tool in supporting children's gross motor development, but it is important to be aware of other factors that influence the outcome